Antithesis and paronomasia in the books of ancient Arabic criticism until the end of the fourth century AH (Abbasid poetry as a model. (Journal of the College of Basic Education, 2024)
The research aims to study two rhetorical arts, namely (antithesis and paronomasia) in Abbasid poetry mentioned in the books of ancient Arabic criticism until the end of the fourth century AH, due to their clear impact in showing the aesthetics of the poetic text in terms of harmony, balance and vocal compatibility that helps create a musical melody that delights the ears before realizing its meaning. The nature of the research required that it be in two sections. The first section dealt with the concept of antithesis and the positions of ancient Arab critics on the poems of the poets of the Abbasid era. While the second section was devoted to explaining the concept of paronomasia and the most important opinions that were prevalent among critics of the poems of the poets of the Abbasid era. Then the research ended with a conclusion that included the most important results that were reached in it, then a list of sources.